(untitled) (Journal of the College of Basic Education, 2022)
The study aims at defining the effectiveness of an educational program according to the social theory in the collection of geography and the development of geographical thinking among the first grade students. In order to achieve the objective of the study, the researcher followed the procedures of the experimental method, adopting one of the experimental designs with partial control, and designing the experimental and control groups with the tribal and post-test. The researcher randomly selected the secondary school for the girls and the secondary units of the national unit of the Directorate of Education Rusafa 1 / Baghdad, for the purpose of application of the experiment was selected Division A to represent the experimental group in the secondary ideas and Division B represents the control group in the national unity unit and the number of sample (72) (35) in the experimental group and (37) in the control group He also prepared an achievement test consisting of (38) paragraphs for the first class. He chose the second course of the course p . The researcher use spss .